Organization and behavior of the synaptonemal complex during achiasmatic meiosis of four buthid scorpions - Schneider, Marielle C.; Mattos, Viviane F. [UNESP]; Carvalho, Leonardo S.; Cella, Doralice M. [UNESP] (Karger, 2014)
Testicular cells of 4 buthid scorpions, Rhopalurus agamemnon (2n = 28), R. rochai (2n = 28), Tityus bahiensis (2n = 6), and T. fasciolatus (2n = 14), which show different types of chromosomal configurations in meiosis I, were subjected to cellular microspreading in order to (1) obtain knowledge about the organization and behavior of the synaptonemal complex (SC), and (2) acquire data about the mechanisms responsible for inter-and intraindividual chromosomal variation within Buthidae. Ultrastructural analysis of microspread nuclei revealed SCs with a well-preserved structure until late substages of prophase I, but did not detect kinetochore plates and recombination nodules. Pachytene cells of R. agamemnon, R. rochai and T. bahiensis exhibited single and unsynapsed axes continuous with totally synapsed SCs, indicating the occurrence of heterozygous chromosomal rearrangements. Although chromosome chains were not observed in T. fasciolatus, the presence of gaps and interlocks points out that this species also carries heterozygous rearrangements, involving a small chromosome segment. Especially in R. rochai, the cellular microspreading analysis was useful to clarify the origin of inter-and intraindividual variation in the number of bivalent-like elements and in the number of chromosomes involved in multivalent associations. It was found that more chromosomes were involved in rearrangements than previously established through investigations using light microscopy alone. (C) 2015 S. Karger AG, Basel
Keywords: Chromosomal rearrangements; Holocentric chromosomes; Multivalent associations; Rhopalurus; Tityus